A Corpus-based Study of Fillers among Native Basque Speakers and the Role of Zera. (September 2014) - Urizar, Xabier; Samuel, Arthur G
Although speakers often transmit their messages clearly and concisely, their speech also includes disfluencies, including filler words. We have analyzed the kinds of filler-like words (hereafter fillers) that native Basque speakers produce and the role that these fillers have within the discourse. We recorded six Basque L1 speakers in a natural setting designed to trigger spontaneous speech. Because Basque is an agglutinative language it may offer speakers certain options for filler use that have not been observed in studies of languages that do not have such a rich agglutinative morphology (e.g. English). When speakers are close to the retrieval of a to-be-produced word, but not quite able to access it, they may use the agglutinative morphology to give the listener clues to the syntactic category of the intended word. In Basque such clues could be provided by modifying the surface form of a filler. Our corpus includes approximately 300 filler tokens. We provide analyses of the kinds of fillers this population produces and the contexts in which these appear. Certain fillers tend to be produced before beginning large units (e.g. sentences), whereas others usually precede smaller units. One filler (/zera/) behaves differently than the others. In particular, it assumes context-based forms that offer listeners partial information about the almost-retrieved word.